2021
DOI: 10.1080/0309877x.2021.1948509
|View full text |Cite
|
Sign up to set email alerts
|

Student fears of oral presentations and public speaking in higher education: a qualitative survey

Abstract: Oral presentations and public speaking are an important aspect of the student experience in the United Kingdom higher education. Many modules (self-contained units normally within a programme of study) use presentations as a form of assessment and require students to verbally engage in small and large group settings to enhance learning. Previous research evidence has indicated that many students experience fear in public speaking. The aims of this qualitative survey were two-fold. First, it sought to gather fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 30 publications
3
49
0
8
Order By: Relevance
“…Learners employ these strategies at varying degrees to help them achieve communicative goals whenever they face problems in their interactions. Grieve et. al (2021), conducted a qualitative study on fears of oral presentations and public speaking among forty-six university students of the West of England University, Bristol.…”
Section: Theory For Communication Strategiesmentioning
confidence: 99%
“…Learners employ these strategies at varying degrees to help them achieve communicative goals whenever they face problems in their interactions. Grieve et. al (2021), conducted a qualitative study on fears of oral presentations and public speaking among forty-six university students of the West of England University, Bristol.…”
Section: Theory For Communication Strategiesmentioning
confidence: 99%
“…However, anxiety plays an important role in oral presentations. Grieve, Woodley, Hunt, and McKay (2021) noted that fear of live performances could hurt a student's university experience and be a factor in mental health and wellbeing issues. Dellah, Zabidin, Nordin, Amanah, and Atan (2020) found that student English proficiency level substantially affected the anxiety felt when speaking.…”
Section: Avoiding Anxiety Through Video Presentationsmentioning
confidence: 99%
“…Another affective factor that influences students' public speaking anxiety is having negative experience in doing public speaking and oral presentation. They might deal with fear of being judged (worried of other people thought); having physical symptoms (shaking hands, tongue-tied, panic attack, getting blushed, dried throat, and sweaty hands); feeling uncertain about the topic discussed that relates to fear of audience negative reaction; and negative effect of students experience in higher education which affects their class interaction and learning process (Grieve et al, 2021). These affective factors either external or internal, can make students feel uncomfortable speaking in front of many people that are usually called as having public speaking anxiety or glossophobia as Hancock et al (2010) refers to.…”
Section: Introductionmentioning
confidence: 99%
“…, andGrieve et al (2021) teachers' evaluation toward students' speaking practice can also develop students' speaking anxiety. The interview finding related to the assessment's pressure on students that in line with those researchers' statements are: -ISSN: 2528-4479, P-ISSN: 2477-5304 http://jurnal.unissula.ac.id/index.php/edulite DOI: http://dx.doi.org/10.30659/e.7.1.82-99 whatever English accent, it is not that simple.…”
mentioning
confidence: 99%